2009
DOI: 10.1017/s0007114509993503
|View full text |Cite
|
Sign up to set email alerts
|

Bovine colostrum supplementation attenuates the decrease of salivary lysozyme and enhances the recovery of neutrophil function after prolonged exercise

Abstract: Oral supplementation with bovine colostrum (COL) has been shown to enhance immunity in human subjects. However, there is limited research on the use of bovine COL supplementation to counter exercise-induced immunodepression, as a model of stress-induced immunodepression, and previous research has focused primarily on salivary IgA. The aim of the present study was to determine the effects of bovine COL supplementation on exercise-induced changes in innate immunity (neutrophil function and salivary lysozyme) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 34 publications
9
85
2
Order By: Relevance
“…If there were any modulatory effects of COL on performance or stress responses, this could also contribute indirectly to effects on the immune responses. However, the present findings of similar leukocyte trafficking, and physiological measures, between groups (along with similar findings in the previous studies that also found no difference in stress hormone responses, e.g., [18,19]), suggest that subjects in this study were exposed to a matched exercise-induced stress, supporting the previous evidence that the effects of COL are not due to such indirect mechanisms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…If there were any modulatory effects of COL on performance or stress responses, this could also contribute indirectly to effects on the immune responses. However, the present findings of similar leukocyte trafficking, and physiological measures, between groups (along with similar findings in the previous studies that also found no difference in stress hormone responses, e.g., [18,19]), suggest that subjects in this study were exposed to a matched exercise-induced stress, supporting the previous evidence that the effects of COL are not due to such indirect mechanisms.…”
Section: Discussionsupporting
confidence: 92%
“…The mechanism(s) behind such effects remain unclear, but it has been proposed that it is linked to COL reducing perturbations in cellular immunity following prolonged exercise [17]. We have previously demonstrated that COL blunts the decrease in blood neutrophil effector functions following prolonged exercise [18,19]. Shing et al [20] observed a prevention of a post-exercise decrease in cytotoxic/suppressor T cells during an intensive period of training.…”
Section: Introductionmentioning
confidence: 93%
“…Although there was no effect on the summed response, there were clear differences at the lowest dose and increased sensitivity in the COL group. Taken together this supports previous evidence from our laboratory where COL has been shown to act as a nutritional countermeasure to the decreased immunity (and increased susceptibility to illness) following prolonged exercise( 1,2) .…”
Section: Resultssupporting
confidence: 90%
“…The NLR is recognized as an index to assess exercise stress (Gleeson and Bishop 2000). Several previous studies have reported that the NLR increases after intense exercise (Nieman et al 1995(Nieman et al , 1999Makras et al 2005;Davison and Diment 2010;Lancaster et al 2003). In the present study, the NLR increased after exercise compared with that at Pre, and the increase continued until 4 h after exercise.…”
Section: Discussionsupporting
confidence: 61%